Cost-effectiveness of osimertinib in the treatment of advanced EGFR-mutated non-small cell lung cancer: a systematic review. (19th May 2022) - Nargesi, Shahin; Dolatshahi, Zeinab; Rezapour, Aziz; Alipour, Vahid; Souresrafil, Aghdas; Farabi, Hiro; Javadmoosavi, Seyed Arash; Safakhah, Mandana; Moradi, Najmeh
ABSTRACT: Background: The most common type of lung cancer is advanced and mutant non-small cell lung cancer (NSCLC). Although targeted tyrosine kinase inhibitors (TKIs) have reconstructed the care of these patients, the resistance of TKIs to the secondary EGFR-T790M mutation in advanced or metastatic NSCLC led to the introduction of the third generation of them, like osimertinib. Osimertinib has represented a remarkable increase in progression-free survival (PFS) and a decrease in death and hazard ratios in patients with required T790 mutation and sensitizing EGFR mutation without T790M. We aimed to evaluate the cost-effectiveness of osimertinib for the treatment of these patients compared to chemotherapy or immunotherapy with the last generations of EGFR-TKIs. Areas covered: Electronic searches were conducted on PubMed, Embase, Science Direct, Scopus, , Web of Knowledge, NHSEED, NHS Health Technology assessment (CRD), and Cost-Effectiveness Analysis Registry databases. Related articles were reviewed from January 2015 to the end of August 2020. Out of 2708 initial studies, 10 articles had the inclusion criteria. Expert opinion: Although osimertinib improves the quality of life and PFS for the mentioned patients based on its greater efficacy compared to standard EGFR-TKIs and chemotherapy, its high cost prevents considering it a cost-effective option. And, since most entered studies have been done in developed countries, it certainly does not true to extend these results to low-income and developing countries. Therefore, further studies in those countries are needed to evaluate the cost-effectiveness of osimertinib for sensitizing EGFR mutation without T790M and required T790M in advanced or metastatic NSCLC.